Dendritic cell‐targeting DNA‐based nasal adjuvants for protective mucosal immunity to Streptococcus pneumoniae. (13th June 2017) - Kataoka, Kosuke; Fukuyama, Yoshiko; Briles, David E.; Miyake, Tatsuro; Fujihashi, Kohtaro
ABSTRACT: To develop safe vaccines for inducing mucosal immunity to major pulmonary bacterial infections, appropriate vaccine antigens (Ags), delivery systems and nontoxic molecular adjuvants must be considered. Such vaccine constructs can induce Ag‐specific immune responses that protect against mucosal infections. In particular, it has been shown that simply mixing the adjuvant with the bacterial Ag is a relatively easy means of constructing adjuvant‐based mucosal vaccine preparations; the resulting vaccines can elicit protective immunity. DNA‐based nasal adjuvants targeting mucosal DCs have been studied in order to induce Ag‐specific mucosal and systemic immune responses that provide essential protection against microbial pathogens that invade mucosal surfaces. In this review, initially a plasmid encoding the cDNA of Flt3 ligand (pFL), a molecule that is a growth factor for DCs, as an effective adjuvant for mucosal immunity to pneumococcal infections, is introduced. Next, the potential of adding unmethylated CpG oligodeoxynucleotide and pFL together with a pneumococcal Ag to induce protection from pneumococcal infections is discussed. Pneumococcal surface protein A has been used as vaccine for restoring mucosal immunity in older persons. Further, our nasal pFL adjuvant system with phosphorylcholine‐keyhole limpet hemocyanin (PC‐KLH) has also been used in pneumococcal vaccine development to induce complete protection from nasal carriage by Streptococcus pneumoniae . Finally, the possibility that anti‐PC antibodies induced by nasal delivery of pFL plus PC‐KLH may play a protective role in prevention of atherogenesis and thus block subsequent development of cardiovascular disease is discussed.